The Experience of Learning a Second Language as an Adult: A Qualitative Exploration of Motivation and Challenges - Mardani, Farzaneh; Vázquez, Nancy Parra; Rajendrakumar, Jinashree; Saadati, Seyed Milad (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This qualitative study aimed to explore the motivations and challenges faced by adults learning a second language. By delving into the personal experiences of adult learners, the study sought to uncover the factors that drive individuals to pursue language learning and the obstacles they encounter in this journey. Methods and Materials: The study utilized a qualitative research design, employing semi-structured interviews with 33 adult learners who had embarked on learning a second language. Participants were selected through purposive sampling to ensure diversity in age, gender, first language, second language being learned, and learning context. Theoretical saturation was achieved to ensure comprehensive coverage of the experiences and perspectives of adult language learners. Thematic analysis was conducted on the interview transcripts to identify themes and subthemes related to motivation and challenges. Findings: Two main themes emerged from the analysis: Motivation and Challenges. Under Motivation, five categories were identified: Personal Fulfillment, Professional Advancement, Cultural Connection, Social Interactions, and Cognitive and Health Benefits. Challenges were categorized into seven themes: Language Complexity, Time Constraints, Lack of Resources, Psychological Barriers, Environmental Factors, Learning Strategies, and Sociocultural Challenges. Each category was supported by several concepts, providing a detailed understanding of the factors influencing adult language learning. Conclusion: The study reveals a complex landscape of motivations and challenges in adult second language acquisition. While motivations ranged from personal growth to professional needs, challenges encompassed both internal psychological barriers and external environmental factors. The findings highlight the importance of tailored support and resources for adult language learners, addressing both their diverse motivations and the multifaceted challenges they face.